The history, context, and beneficiaries of the enterprise rehabilitation financing (ERF) under the small business corporation (SBCorp): The case of super-typhoon Yolanda (2013-2015) - Magpayo, Jacco Miguel M (Animo Repository, 2024)
Small Business Corporation (SBCorp) is a government institution that was established in 1992 after the Republic Act No. 6977 was signed into law in 1991. This study focuses on the history of Small Business Corporation’s program, the Enterprise Rehabilitation Financing (ERF); this program was formed and institutionalized after Typhoon Yolanda in 2013. Provided in this study is the historical context and legal foundations of the Small Business Corporation from 2013 to 2015. This study also assessed the severity of the damages from Typhoon Yolanda and how it led to the creation of the ERF program. To strengthen the study, Oral History was used to provide information from the businessowners’ (Peter Holaysan, Mareche Barrite, Keith Lozada, Bryan Santillian, and Schubert Dichos) experience with the ERF program; and from the officers (Odette Baula and Francisco Buenavides) who were part of SBCorp for the ERF program after the onslaught of Typhoon Yolanda. This study added to the institutional history of Small Business Corporation despite the institution having limited sources.